2009
DOI: 10.1007/978-3-642-00267-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Optimization for Multiobjective Portfolio Selection under Markowitz’s Model with Application to the Caracas Stock Exchange

Abstract: Abstract. Several problems in the area of financial optimization can be naturally dealt with optimization techniques under multiobjective approaches, followed by a decision-making procedure on the resulting efficient solutions. The problem of portfolio optimization is one of them. This chapter studies the use of evolutionary multiobjective techniques to solve such problems, focusing on Venezuelan market mutual funds between years 1994 and 2002. We perform a comparison of different evolutionary multiobjective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Such constraints make the use of the CLA very difficult or impracticable. In this kind of problems, both SPEA 2 and NSGA II have been references in the literature, and they usually present consistently better results than alternative techniques - (Duran, Cotta, & Fernández, 2009), (Mishra, Panda, Meher, & Sahu, 2009), (Metaxiotis & Liagkouras, 2012).…”
Section: Multiobjective Evolutionary Algorithms Applied To Portfolio mentioning
confidence: 99%
“…Such constraints make the use of the CLA very difficult or impracticable. In this kind of problems, both SPEA 2 and NSGA II have been references in the literature, and they usually present consistently better results than alternative techniques - (Duran, Cotta, & Fernández, 2009), (Mishra, Panda, Meher, & Sahu, 2009), (Metaxiotis & Liagkouras, 2012).…”
Section: Multiobjective Evolutionary Algorithms Applied To Portfolio mentioning
confidence: 99%
“…Also, evolutionary algorithms can easily be used with various risk measures because, contrary to methods such as linear or quadratic programming, they do not rely heavily on specific properties of the evaluation function. Apart from optimization of portfolio parameters [11], evolutionary portfolio optimization has been used in the literature for other problems such as tracking a stock market index [2] or replicating the behaviour of an investment fund [17].…”
Section: Introductionmentioning
confidence: 99%
“…The results were shown that MOCeLL outperforms the other algorithms. Duran et al (2009) performed a comparison of different evolutionary multiobjective approaches, namely NSGA-II, SPEA2, and indicator-based evolutionary algorithm (IBEA) (Zitzler and Kunzli, 2004). They have used a binary solution representation for all algorithms.…”
Section: The Classical Mean-risk Portfolio Problemmentioning
confidence: 99%